Psychological Support for Overcoming the Consequences of Aggressive Behavior - Ivanov S. (Клиническая и специальная психология, 2018)
This article describes the meaning of the terms „aggression“, „aggressive“ and „aggressive behavior“. It specifies the nature and basic principles of psychological counseling. It aims to present techniques and best practices for overcoming the consequences of aggressive behavior. It describes a number intervention methods such as separation of the role functions from the personal reactions; progressive muscle relaxation, pragmatism to the manifestations of undesirable behavior, breathing techniques, visualization of positive images, method of biological feedback, meditation, neuro-linguistic programming, realistic approach to events, situations and persons involved in them, clear definition of their capabilities and competencies. These ways of influence are illustrated by describing two specific cases. They are suitable for both individual and group counseling. An examination of the symptoms and consequences of the aggressive behavior provides essential information on the experiences of the counselor’s clients as well as their relationship to the past, present and future.